Corporate governance: Nominee director the gatekeeper / Yang Chik Adam - Adam, Yang Chik (Research Management Institute (RMI), 2015)
The term corporate governance has been defined in the broad sense and is also referred to as the process through which shareholders induce management to act in their interest A nominee director is usually appointed by the nominators to sit on the board of directors of a company to represent their interests. These nominators are usually the major shareholders or a class of shareholders or the creditors. Nominee directors are commonly found in companies such as in corporate groups, joint ventures and government-linked companies. It is a trite law that the board of directors act in the best interest of the company. A nominee director, in discharging his or her duties to the company will face the dual loyalty. Firstly is his or her loyalty to the nominators who have nominated him or her to represent their interest in the company. Secondly is the nominee director s duty to the company. Hence, the nominee director is in a delicate position in discharging his or her duty. Section 132(1E) of the Malaysian Companies Act 1965, stipulates the position of the nominee director under the strict approach that is to act in the best interest of the company and shall not subordinate the interest of the company to his or her nominators. Malaysian corporate ownership is in the concentrated category and the position of nominee directors is common. Companies in Malaysia are required to adhere to the Malaysian Code on Corporate Governance 2012. This paper aims to provide clearly the position of the nominee director as the gatekeeper and will assist the corporate regulators to improve and promote good corporate governance practice in the Malaysian corporate landscape.